THE INFLUENCE OF GROUP GUIDANCE SERVICES ON STUDENTS' AGGRESSIVE BEHAVIOR AT SMA NEGERI 1 LAWA - Adriyanti Susanti Sero (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2023)
This study aims to determine the effect of group guidance services on students' aggressive behavior at SMA Negeri 1 Lawa in the 2020/2021 school year. This research was conducted using a quantitative method, by taking a sample of 65 students of SMA Negeri 1 Lawa in the academic year 2020/2021. Data were collected through a questionnaire with a Likert scale. The data analysis technique used simple linear regression analysis with the help of a computer program SPSS 23 for windows. The results showed that there was an effect of group guidance services on students' aggressive behavior. The regression equation Y = 4.525 - 0, X with the quantitative increment of the two variables was 1: 0.110, this comparison shows that if there is an increase of one time / unit in the group guidance service variable. (X) there will be a decrease of 0.761 in the student's aggressive behavior variable (Y). The regression equation is significant or will not be tested using the Fcount value at the significant level of 0.05. Meaning that Ha was accepted and Ho was rejected. The conclusion is that the hypothesis that says there is an effect of group guidance services on students' aggressive behavior at SMA Negeri 1 Lawa is accepted and significant, this is indicated by the value of the regression coefficient (F) of 53,595 with a significant of 0,000